Baby Massage Theraphy in Improving Breastfeeding Production and Bounding Attachment Between Mom and Baby in Primipara Postpartum Mother - Sholikhah (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Research on infant massage on breast milk production and Bounding Attachment was carried out because there were still many primipara postpartum mothers whose breast milk was not fluent, therefore the researcher took a study on infant massage on breast milk production and bounding attachment in the work area of Mojogedang II health center. Massage is a tactile stimulation that has biochemical and physiological effects in the baby, increase infant weight, and stimulate milk production. Purpose To prove whether baby massage can increase milk production and Bounding Attachment in primipara postpartum mothers. Method This research type is Quasi Experiment with Purposive sampling. Test analysis used is General Linier Model Repeted Measure Anova. Results The average increase in breast milk infant massage intervention was 24,34 ml while the control group was 2,67 ml. The average increase in infant massage infant weight gain was 0,13 grams while in the control group was 0,06 grams. The average increase in bounding attachment for the infant massage intervention group was 5,13 while in the control group was 0. The p value is > 0,05. Conclusion From the results of the study stated that there was a difference in the average increase in milk production, infant weight and bounding attachment between treatment and control groups, namely in the treatment greater than the control group, the value of p > 0.05 means the hypothesis was not accepted.